Managing dam breach and flood inundation by HEC-RAS modeling and GIS mapping for disaster risk management - Aung Pyae Phyo; Helmut Yabar; Delmaria Richards (Case Studies in Chemical and Environmental Engineering, 2023)
Dam breaks lead to loss of lives plus economic and environmental damages. However, with technological advancements in quantitative research, dam safety management (DSM) can be improved to mitigate mass damage to lives and properties. This study aims to predict the breach outflow hydrograph and prepare downstream flood inundation maps for the flood-prone areas around the Swa Chaung Dam. In this research, the authors emphasized other essential input data such as land use land cover, soil type, curve number, and differences in analytical simulation utilizing 1D and 2D to enhance the body of work. For classifying the dam size, the ICOLD Large Dams Classification and USACE Dams Size Classification Criteria were used because they match Myanmar's condition for hazard potential and inflow design flood. This research's central theme is comparing different flood return periods through analytical simulation methods. Three inflow design floods, 5000 - and 10,000-year return floods, and probable maximum flood (PMF) were applied in rainfall-runoff calculations using the Hydrologic Engineering Center-Hydrological Modeling System (HEC-HMS). The maximum discharge for the flood returns years and PMF were 19,606.51 m3/s, 25,903.53 m3/s, and 36,769.99 m3/s, respectively. 1D and 2D unsteady flow analyses were simulated by applying the Hydrologic Engineering Center-River Analysis System (HEC-RAS). The maximum floodwater depth were 16.13 m and 22.02 m, the affected areas were 45.52 m2 and 58.23 m2, and the affected villages were 16 and 32 for 1D and 2D, respectively. The results from 2D were more detailed and covered more flooded areas than 1D. Therefore, the emergency preparedness plan can be made by using 2D results. Accordingly, floodplain management strategies can easily support downstream areas. Furthermore, mitigation measures can enhance food security, energy, and water sanitation, commonly adversely affected by flood water.